The Influence of Simple Respiratory System Media on Students’ Learning Outcomes in Class V Science and Science Subjects at SD GMIT Airnona 1 Kupang - Batmaro, Mardini Y.L; Tanggur, Femberianus S.; Nahak, Kristina E. Noya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The aim of the research was to determine the effect of simple respiratory system media on student learning outcomes at SD GMIT Airnona 1 Kupang. This type of research is Quasi Experimental Design in the form of Nonequevalent Control Group Design. The population of all fifth-grade students at SD GMIT Airnona 1 Kupang is 24 students, with a sample size of 24 students and data collection techniques using observation, documentation and multiple-choice test questions. Data were analyzed using hypothesis testing and t-test. The results of the research show that the average posttest for the experimental class and control class using the t-test was 82.08>53.75 with a difference of 7.525. Furthermore, through hypothesis testing (paired samples test), it shows that the sig (2-tailed) t-test for equality of means is 0.000 < 0.05, meaning that Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence of the influence of simple respiratory system media on learning outcomes in science and science subjects in class V of SD GMIT Airnona 1 Kupang.